Upaya Memperlancar Distribusi Air Bersih Ke Instalasi dalam Bangunan di Program Studi Pendidkan Teknik Bangunan - Wiratno Wiratno; Samuel Layang; Petrisly Perkasa; Muhammad Adam Malik; Donny Setiawan (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Building Engineering Education Study Program is part of the Faculty of Teacher Training and Education (FKIP) of Palangka Raya University which has facilities and infrastructure to support teaching and learning activities. There are several problems faced by partners, especially clean water installations. The clean water installation consists of a toren (water reservoir) and a pipe network. The water pressure that comes out through the faucet is relatively small. This problem is very important to be resolved because the availability and smooth running of water is an absolute necessity during the COVID-19 pandemic. To prevent and break the chain of the spread of COVID-19, it is necessary to apply health protocols properly, one way is to wash hands frequently, which of course requires the availability of water. The solution offered to overcome this problem is to add an air pipe (ventilation). The addition of an air pipe can increase the flow of water. The increase in water discharge at point 1 is 25.93%, at point 2 is 1.98%.